A Novel msDNA (Multicopy Single-Stranded DNA) Strain Present in Yersinia frederiksenii ATCC 33641 Contig01029 Enteropathogenic Bacteria with the Genomic Analysis of It's Retron. (17th November 2011) - Das, Rasel; Shimamoto, Tadashi; Arifuzzaman, Md.
Abstract : Retron is a retroelement that encodes msDNA (multicopy single-stranded DNA) which was significantly found mainly in Gram-negative pathogenic bacteria. We screened Yersinia frederiksenii ATCC 33641 contig01029 for the presence of retroelement by using bioinformatics tools and characterized a novel retron-Yf79 on the chromosome that encodes msDNA-Yf79. In this study, we perceived that, the codon usage of retron-Yf79 were noteworthy different from those of the Y. frederiksenii genome. It demonstrates that, the retron-Yf79 was a foreign DNA element and integrated into this organism genome during their evolution. In addition to this, we have observed a transposase gene which is located just downstream of retron-Yf79. So, the enzyme might be responsible for the transposition of this novel retron element.